Perception of Indian citizens regarding lockdown during COVID-19 pandemic in the Indian context - Shraddha S Kulkarni; Maya Nannaware; Samir Singru; Vaishali P Bansod; Col P S Chawla; Khyati Kalra (MGM Journal of Medical Sciences, 2023)
Background: In response to coronavirus disease 2019 (COVID-19), the government of India declared a lockdown on March 24, 2020. This affected the daily life of citizens, influencing the availability of daily needs. There was a diverse opinion among public health experts regarding the implementation of the lockdown. Therefore, this study was planned to assess the perceptions and to study the effects of lockdown and challenges faced by Indian citizens during the lockdown imposed during the COVID-19 pandemic. Materials and Methods: A cross-sectional study was carried out among Indian citizens above 18 years old using the snowball sampling method. Data were collected through Google forms containing a semistructured questionnaire. Results: Of 464 participants, 61.85% of them reported that lockdown is necessary to contain the spread of the coronavirus infection; 50.43% had a negative effect on their job; and felt mental health problems like anxiety, lack of sleep, stress due to increased workload, and the feeling of separated from family. Conclusion: According to the majority of participants, the lockdown was necessary to contain the spread of the pandemic. Participants who faced different problems also found ways to overcome them in a positive way.